Design and Analysis of Planetary Wheeled Stair-climbing Wheelchair - Weibin Zhang; Wei Tang (Jixie chuandong)
Aiming at safe stairs climbing and efficient locomotion on the ground for aged or physical disabled people, a planetary wheeled electric powered wheelchair (EPW) is designed and the composition of the wheelchair mechanism, control system scheme and its functional characteristics are introduced in detail. Through establishing the dynamic model of the planetary wheel clusters based on the Lagrange equation, the angle acceleration curves with various given equivalent torques are studied, the stability margin of the EPW is analyzed in detail in the process of a single step climbing which has demonstrated that the anti-tip-over bracket can effectively enhance the stability. The planetary wheeled stair-climbing wheelchair can effectively help those who are in need and meet the actual needs of daily travel and climbing stairs.